Efficacy and safety of oral low-dose glucocorticoids in patients with estrogen-dependent primary osteoarthritis (2014)
Estrogen-dependent osteoarthritis (EDPOA) is a disease of perimenopausal-age women. Their manifestations are polyarticular pain with common co-morbidities (carpal tunnel syndrome, insomnia, fatigue, depression, and fibromyalgia). Based on dual role of glucocorticoids, its trophic action on the chondrocyte and its anti-inflammatory effect, we conducted a prospective interventional cohort study where we evaluate the efficacy and safety of oral low-dose GC in one hundred women with EDPOA. The pain intensity, number of tender joints as well as impact in co-morbidities were analyzed. We conclude that the use of low-dose GC in patients with EDPOA can be an effective and a safe therapeutic option. © 2013 Springer-Verlag.